Variability of selected parameters as a result of microwave disintegration of sewage sludge - Czajkowska, Justyna; Nowak, Piotr; Malarski, Maciej; Pergół, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains the results of research carried out at the SGGW Water and Sewage Institute in Warsaw regarding the pre-treatment of sewage sludge by means of microwave disintegration. Sewage sludge came from the "Mokre Łąki" sewage treatment plant in the Izabelin commune. Experiments were carried out on thickened and unthickened sludge. Every sludge was disintegrated in portions of various volumes, as well as at different times of microwave influence.
Keywords: sewage sludge; disintegration; sludge sonification